Purine alkaloid producing cell cultures: fundamental aspects and possible applications in biotechnology - Prenosil, J. E.; Hegglin, M.
Coffea arabica is one of the plant species that has been widely studied with attention largely being given to its secondary products, caffeine and other purine alkaloids. The biosynthesis and significance of these alkaloids for the plant are elucidated and presented. Tissue cell culture and fundamental aspects of cell growth and alkaloid productivity are also discussed. The feasibility of Coffea cultivation in cell suspension has recently attracted the interest of many researchers. Although this cultivation is not of commercial interest, Coffea is especially suitable as a model cell line for reaction engineering studies because the purine alkaloids are well-characterised and readily released in culture medium. The use of free and immobilized coffee cells in various types of bioreactors (stirred tank, expanded bed, and membrane device)is shown.
Keywords: COFFEA ARABICA; PURINE ALKALOIDS; CAFFEINE; BIOREACTORS